An 8 cm long holmium-doped fiber saturable absorber for Q-switched fiber laser generation at 2-µm region - Rahman, Mohd Fauzi Ab; Dhar, Anirban; Das, Shyamal; Dutta, Debjit; Paul, Mukul Chandra; Rusdi, Muhammad Farid Mohd; Latiff, Anas Abdul; Dimyati, Kaharudin; Harun, Sulaiman Wadi (Elsevier, 2018)
We demonstrate a Q-switched all-fiber laser operating at 2-µm region by adding a piece of 8 cm long holmium doped fiber (HDF) as a fiber saturable absorber (SA) in Thulium doped fiber laser (TDFL) ring cavity. Doping of Ho ions into yttria-alumina silica glass was done through conventional Modified Chemical Vapor Deposition (MCVD) technique in conjunction with solution doping process. The fabricated HDF has a linear absorption of 3 dB with a core diameter and a numerical aperture of 10 µm and 0.18, respectively. A self-started Q-switching operation begins at 418 mW pump level and continually dominant until 564 mW pump level. As the pump power increases, stable pulse train presence from 30.61 kHz to 38.89 kHz while the pulse width reduces from 3.18 µs to 2.27 µs. Both maximum output power and maximum peak power are obtained at 5.05 mW and 57.2 mW, respectively, while the maximum pulse energy is calculated to be 129 nJ. The signal-to-noise ratio (SNR) of the fundamental frequency is 50 dB. Our work may contribute to the discovery of stable, robust, and economic SA for pulse fiber laser generation at 2-µm region.